HUBUNGAN BERSYUKUR DAN PERILAKU PROSOSIAL TERHADAP EFIKASI DIRI PADA PELAKU USAHA MIKRO, KECIL, DAN MENENGAH (UMKM) KOTA DENPASAR - Wirama, I Nyoman Angga; Wulanyani, Ni Made Swasti (Jurnal Psikologi Udayana, 2016)
Indonesia has 248 million people, with the unemployment rate continues to rise each year (BPS, 2014). Business actor is a figure capable of promoting the country's economy and is able to open up job vacancy. Many successful entrepreneurs start micro, small and medium enterprises (UMKM). UMKM is the basis for the country's economy due to the fact that from the 52.76 million business units, 99% of which are UMKM. Business actor is a tough profession and friends with uncertainty. High self-efficacy is required to be a successful business operators. Grateful and prosocial behavior influence and form a self-efficacy into a more positive. Grateful can make someone have positive information about himself, positive psychological state, physically healthy, and a sense of optimism. Prosocial behavior creates life satisfaction, sense of accomplishment in a person, and improve the quality of self. This research was conducted in the city of Denpasar by using snow ball sampling. This research is a quantitative research using multiple regression analysis to test the hypothesis. A total of 243 UMKMs of Denpasar become respondents in this study. Measuring instrument used is the scale of Gratitude with a reliability coefficient of 0871, Prosocial Behavior scale with reliability coefficient of 0914, and Self-Efficacy scale with reliability coefficient of 0918. The results of data processing indicate that the value of F test = 87 370 (p <0.05), so it can be concluded that there is a relationship between gratitude and prosocial behavior toward self-efficacy on UMKM in Denpasar. The correlation coefficient of 0.507 indicates grateful and prosocial behavior influence amounting to 50.3% on the efficacy. The higher grateful and prosocial behavior owned by UMKM businessmen of Denpasar , the higher their self efficacy.Keywords: Grateful, Prosocial, Self Efficacy, UMKM